2010
DOI: 10.1021/jp1058403
|View full text |Cite
|
Sign up to set email alerts
|

Geometry, Electronic Properties, and Hydrogen Adsorption Properties of Li3N-Based Nanostructures

Abstract: Recent studies of hydrogen storage have focused on lithium metal atoms as dopants in a variety of substrates as Li is the lightest metallic element in the periodic table. In this work, we have explored the role of Li3N nanostructures in hydrogen storage as they possess Li atoms with varying degrees of coordination. We have performed detailed calculations of geometries, electronic structures, and hydrogen adsorption properties of free (Li3N) n (n = 1−7) clusters and those supported on BN nanoribbons by using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…To understand the adsorption mechanism, we calculated the charge distribution in Li doped g-C 3 N 4 using the natural bond orbital (NBO) analysis, which has been found to be more accurate than standard Mulliken analysis or alternative theoretical approaches [31]. Li site is found to carry a charge of 0.774 |e|, suggesting that the bonding between Li and the g-C 3 N 4 is essentially ionic, and the positively charged Li ions would produce local electric field which would polarize H 2 molecules and enhance the adsorption [32][33][34][35][36][37][38].…”
Section: E E Cluster E H E H Cluster = + −mentioning
confidence: 99%
“…To understand the adsorption mechanism, we calculated the charge distribution in Li doped g-C 3 N 4 using the natural bond orbital (NBO) analysis, which has been found to be more accurate than standard Mulliken analysis or alternative theoretical approaches [31]. Li site is found to carry a charge of 0.774 |e|, suggesting that the bonding between Li and the g-C 3 N 4 is essentially ionic, and the positively charged Li ions would produce local electric field which would polarize H 2 molecules and enhance the adsorption [32][33][34][35][36][37][38].…”
Section: E E Cluster E H E H Cluster = + −mentioning
confidence: 99%
“…They have found that the average optimal adsorption enthalpy should be in the range of 0.1-0.2 eV/H 2 . 21,22 It is seen that our designed materials satisfy the criteria for the gravimetric density of hydrogen in storage media by the DOE as well as above the predicted optimal energy window for hydrogen adsorption. Therefore diamondoid-Li/Li + complexes might be good candidates for hydrogen storage materials.…”
Section: Introductionmentioning
confidence: 68%
“…In all our calculations, it was observed that due to the very high stability of ADM, 31 the binding energy of hydrogen molecules on such compounds was very small, i.e., on the order of ∼−0.001 eV, which is out of the energy range from −0.1 to −0.2 eV desirable for reversible H 2 adsorption/desorption near room temperature for hydrogen storage applications. 21,22 Hence, pristine diamondoids are not considered to be good candidates for hydrogen storage applications. However, experimentally it has been shown that by treating the surfaces of diamondoids with chemical solutions, 32-36 the hydrogen atoms of diamondoids can be selectively replaced by other compounds or elements, resulting in significant changes in their electronic structures.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike these composites, however, the nanofibres do not suffer from the gravimetric capacity penalty imposed by an inactive component. Computational studies have demonstrated that pseudo-molecular (Li 3 N) n ( n = 1–7) clusters would bind H 2 via coordinatively unsaturated Li atoms with an adsorption energy approximately an order of magnitude smaller than that of the bulk material 34 . By extension, earlier DFT calculations show that the most favourable adsorption sites for both H 2 and dissociated H atoms are to N positions on the (001) surface of Li 3 N 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike these composites, however, the nanofibres do not suffer from the gravimetric capacity penalty imposed by an inactive component. Computational studies have demonstrated that pseudo-molecular (Li 3 N) n (n = 1-7) clusters would bind H 2 via coordinatively unsaturated Li atoms with an adsorption energy approximately an order of magnitude smaller than that of the bulk material 34 Calculations on nanostructured α-Li 3 N electronic properties. Electronic properties were computed on α-Li 3 N using DFT to compare the behaviour of a monolayer of Li 3 N with respect to the bulk material and to develop an understanding of the evolution of electronic structure with the number of layers as compared to graphene and other van der Waals nanostructures (vdWNs).…”
Section: Synthesis and Characterisation LI 3 N Nanocrystals Grow Folmentioning
confidence: 99%